2016
DOI: 10.21062/ujep/x.2016/a/1213-2489/mt/16/3/600
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ABI Technique and Standard Methods in Measuring Mechanical Properties of Aluminium Al-aloys

Abstract: Mechanical properties and chemical composition of aluminium alloys were investigated by automated ball indentation tests, scanning electron microscopy and energy dispersive X-ray analysis. In this work, Automated Ball Indentation (ABI) technique was compared with the standard mechanical tests. ABI method is based on the load controlled multiple indentations into a polished surface by a spherical indenter. The indentation depth is progressively increased to a maximum user specified limit with intermediate parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…ABI is suitable for finding coefficients of a power law hardening material model, by calculating a stress-strain curve from the indentation diameter, the indenter diameter, applied load and a correlation parameter, which is found iteratively. The strain Puchnin et al 109 and Patil et al 112 Ammar et al 108 and Wang et al 110 Kulkarni et al 114 Bespoke specimens Knitel et al 181 Kazakeviciute et al 188 hardening exponent can be found to within 2% of the actual value. 101 There was a linear correlation between small punch strain hardening index (calculated from maximum load and limit load) and tensile test strain hardening index, which allowed to convert one into another.…”
Section: Plastic Behaviourmentioning
confidence: 90%
“…ABI is suitable for finding coefficients of a power law hardening material model, by calculating a stress-strain curve from the indentation diameter, the indenter diameter, applied load and a correlation parameter, which is found iteratively. The strain Puchnin et al 109 and Patil et al 112 Ammar et al 108 and Wang et al 110 Kulkarni et al 114 Bespoke specimens Knitel et al 181 Kazakeviciute et al 188 hardening exponent can be found to within 2% of the actual value. 101 There was a linear correlation between small punch strain hardening index (calculated from maximum load and limit load) and tensile test strain hardening index, which allowed to convert one into another.…”
Section: Plastic Behaviourmentioning
confidence: 90%